2013
DOI: 10.1097/iae.0b013e3182647f69
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Differences in Pharmacokinetics and Pharmacodynamics Between Four Distinct Formulations of Triamcinolone Acetonide

Abstract: Triamcinolone acetonide formulations do not have the same pharmacokinetics/pharmacodynamics. Kenalog has the longest vitreous visibility and durability. Particle size appears to correlate with efficacy and durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
0
24
0
2
Order By: Relevance
“…10 Previous studies found that the physical properties of Triesence were different from those of Trivaris, which leads to different intraocular pharmacokinetics. 21,22 This may imply a different effectiveness and safety profile for treatment of macular edema from both drugs. There have been no published clinical data on the safety and efficacy of intravitreal Triesence in the treatment of macular edema in a clinical setting.…”
Section: Introductionmentioning
confidence: 96%
“…10 Previous studies found that the physical properties of Triesence were different from those of Trivaris, which leads to different intraocular pharmacokinetics. 21,22 This may imply a different effectiveness and safety profile for treatment of macular edema from both drugs. There have been no published clinical data on the safety and efficacy of intravitreal Triesence in the treatment of macular edema in a clinical setting.…”
Section: Introductionmentioning
confidence: 96%
“…This has led to the development of preservative-free triamcinolone preparations including Triescence (Alcon, USA) and Trivaris (Allergan, USA). However, these preparations have different pharmacokinetic properties resulting in a shorter duration of action than Kenacort 40 [Zacharias et al 2013].…”
Section: Triamcinolonementioning
confidence: 99%
“…There appears to be a significant difference in the pharmacokinetics and pharmacodynamics between different triamcinolone acetonide preparations with increased particle size correlating with increased durability and efficacy [67]. A new, simple technique of using centrifugeconcentrated IVTA (Triesence) found triamcinolone to be present in the vitreous for a median of 3 months longer compared to non-concentrated IVTA [68].…”
Section: Triamcinolone Acetonidementioning
confidence: 99%